STUDY OF THE PHARMACOLOGICAL ACTIVITY OF NOVEL EPOR/CD131 HETERORECEPTOR AGONISTS IN MICE WITH ENDOTHELIAL-SPECIFIC EXPRESSION OF MUTANT POLG GENE - М. В. Korokin; M. V. Kubekina; A. V. Deykin; O. V. Antsiferov; V. M. Pokrovskii; L. V. Korokina; N. L. Kartashkina; V. A. Soldatova; E. V. Kuzubova; A. I. Radchenko; M. V. Pokrovskii (Фармация и фармакология (Пятигорск), 2021)
The aim of the research was to study antiatherosclerotic and endothelial kinds of a protective activity of peptides mimicking an erythropoietin a-helix B tertiary structure with laboratory codes EP-11-1 (UEHLERALNSS), EP-11-2. (UEQLERALNCS), EP-11-3 (UEQLERALNTS).Materials and methods. The study was conducted on 96 C57Bl/6J male double transgenic Polgmut/mut/Cdh5-CRE mice. Atherosclerosis was induced by a balloon injury accompanied by Western diet. Then, for 27 days, the drugs under study were administered once per 3 days at the dose of 20 μg/kg. On the 28th day, the animals were euthanized and the area of atherosclerotic plaques was collected for an assessment. The expression of genes associated with the processes of inflammation, apoptosis, and angiogenesis was determined in the tissues of the aorta. In addition, the endothelial protective effect of peptides in isolated segments of the thoracic aorta of wild and transgenic ransgenic Polgmut/mut mice was studied.Results. The assessment of the plaque size in the animals with the Polgmut/mut/Cdh5-CRE genotype against the background of the peptides under study did not reveal statistically significant differences in comparison to control. However, a quantitative PCR showed a statistically significant decreased expression of pro-apoptotic factors p-53 and Bax, and also increase the expression of anti-apoptotic factor Bcl-2 against the background of the peptides EP-11-1 and EP-11-2 administration. The administration of EP-11-1 and the original peptide pHBSP resulted in a statistically significant decrease in the Bax/Bcl-2 ratio. Compounds EP-11-1, EP-11-2, and EP-11-3 were more effective than the original peptide pHBSP, in reducing the increased expression of genes for inflammatory markers iNos, intercellular adhesion molecules Icam-1, Vcam-1 and E-selectin. The use of EP-11-1 led to a more efficient, in comparison with pHBSP, restoration of endothelial-dependent vasodilation of the aortic segments in mice with endothelial-specific overexpression of the mutant Polg gene.Conclusion. The study carried out on a murine model of the endothelial-specific expression of mutant gamma polymerase has shown that derivatives of the pHBSP peptide with laboratory codes EP-11-1, EP-11-2, EP-11-3, obtained by BLAST-searching for groups of pHBSP related peptides, have atheroprotective and endothelial protective kinds of a protective activity, which is more pronounced in comparison with the original peptide pHBSP.